2020
DOI: 10.47679/jopp.022.12200006
|View full text |Cite
|
Sign up to set email alerts
|

The role of religious coping as a moderator of the relationship between psychological burden and quality of life among caregiver of women with breast cancer

Abstract: Penelitian ini bertujuan untuk mengetahui hubungan antara beban psikologis dengan kualitas hidup yang dimoderatori oleh koping religius pada caregiver wanita dengan kanker payudara. Subjek penelitian ini berjumlah 70 responden yang merupakan caregiver keluarga wanita dengan kanker payudara di Ruang Instalasi Kanker Terpadu “Tulip” RSUP Dr. Sardjito. Terdapat tiga alat ukur yang digunakan dalam penelitian diantaranya WHOQOL-BREF yang sudah diadaptasi sebelumnya ke dalam bahasa Indonesia untuk mengukur kualitas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Female prisoners who cannot adapt to change will experience anxiety (Medley, 1980;Salim et al, 2016). The results showed that most prisoners experienced anxiety in early adulthood (Osasona & Koleoso, 2015., Harlianty, R., & Paramastri, I. 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Female prisoners who cannot adapt to change will experience anxiety (Medley, 1980;Salim et al, 2016). The results showed that most prisoners experienced anxiety in early adulthood (Osasona & Koleoso, 2015., Harlianty, R., & Paramastri, I. 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Religion can also influence the link between depression and QOL [68]. Religious ideas and practices frequently offer individuals religiously appropriate coping methods [69,70]. Inner faith is connected to resilience, QOL, and fewer previous suicide attempts.…”
Section: The Moderated Role Of Religiosity and Social Connectednessmentioning
confidence: 99%
“…Cervical cancer is a malignant cancerous cell that grows in the cervix caused by Human Papilloma Virus (HPV). There are 100 types of HPV that can infect humans and 2 of them are often the cause of cervical cancer namely HPV16 and HPV18 ( Dunleavey, 2008;Harlianty, R., & Paramastri, I. 2020).…”
Section: Introductionmentioning
confidence: 99%